2014
DOI: 10.4236/ijg.2014.510094
|View full text |Cite
|
Sign up to set email alerts
|

Controls on Gosaikunda Lake Chemistry within Langtang National Park in High Himalaya, Nepal

Abstract: Surface water samples and lake bed sediments were collected and analyzed from Gosaikunda Lake within Langtang National Park (28˚05'N, 85˚25'E; 4380 m a.s.l.) in the central Himalayan region of Nepal during fall 2011. The major cations and anions in equivalents were present in the following order:, respectively. Sulfide oxidation coupled with carbonate dissolution and aluminosilicate dissolution appeared to be the dominant geochemical processes determining lake water dissolved ions. Sulfate concentration was mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Globally, Ca is often the most dominant cation in freshwater bodies (Wetzel, ). This finding is consistent with previous studies conducted in a number of freshwater bodies across Nepal (Jones, Knowlton, & Swar, ) including those in the high mountain lakes and rivers (Bhatt, Bhatt, & Gaye, ; Gurung et al., ; Paudyal et al., ; Reynolds, Chapman, French, Jenkins, & Wheater, ; Tuladhar et al., ). Mg also has significant contribution to cationic concentration in Lake Rara (Table ) resulting in a different water chemistry type (Ca(Mg)HCO 3 ) from those of other water bodies in the eastern and central region.…”
Section: Discussionsupporting
confidence: 92%
“…Globally, Ca is often the most dominant cation in freshwater bodies (Wetzel, ). This finding is consistent with previous studies conducted in a number of freshwater bodies across Nepal (Jones, Knowlton, & Swar, ) including those in the high mountain lakes and rivers (Bhatt, Bhatt, & Gaye, ; Gurung et al., ; Paudyal et al., ; Reynolds, Chapman, French, Jenkins, & Wheater, ; Tuladhar et al., ). Mg also has significant contribution to cationic concentration in Lake Rara (Table ) resulting in a different water chemistry type (Ca(Mg)HCO 3 ) from those of other water bodies in the eastern and central region.…”
Section: Discussionsupporting
confidence: 92%
“…The studies conducted by Lofler in 1969 in high-altitude lakes in the Khumbu Himalayan Region (4,500-5,600 m a.s.l) presented general information on lakes in Nepal and its physical characteristics and those conducted in Rara Lake (2,990 m a.s.l) by Okino and Satoh (1986) described physical features, productivity and composition of the lake biomes in a limited study samples were the first research attempts for highelevation lakes in Nepal (Rai 2000;Sharma et al 2005). The analysis of hydro-chemistry from Gosaikunda Lake, situated at 4,380 m a.s.l, revealed that, despite being influenced by human activities, the lake is still oligotrophic and pristine (Bhatt et al 2014). However, Rupa Lake, situated at an altitude of 600 m a.s.l in western Nepal is highly altered and is currently a eutrophic lake due to high nutrient values in the lake water and higher biomass levels that were revealed in a study conducted by (Kunwar and Devkota 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We found sulfate concentration many times higher than in most of the largest river systems of the world and in the fastest weathering regimes of a silicate terrane on the earth surface (McDowell and Asbury 1994;Meybeck and Ragu 1997;Gaillardet et al 1999;Bhatt and McDowell 2007;Tartai et al 1998;Bhatt et al 2014a). Takeuchi et al (2012) found that various organisms such as insects, copepods, and algae live in ponds in the debris-covered area of this glacier.…”
Section: Overview and Composition Of Major Ionsmentioning
confidence: 99%
“…The concentrations of DOC in supraglacial ponds appeared nearly the same as river water samples in high-altitude areas of the same region but the export rate of DOC calculated threefold higher in low-elevation sites of the LangtangNarayani river system than the high-elevation sites in the same area (unpublished data). The DOC of these supraglacial ponds is threefold lower than a pond in the Kathmandu valley, Nepal, and tenfold lower than a heavily urbanized basin (Bagmati River) in the Kathmandu valley, probably due to difference in vegetation, anthropogenic inputs, and temperature (Bhatt et al 2013(Bhatt et al , 2014b. The alkalinity of supraglacial ponds appeared comparable with the Tatra basin of Europe and lower than the Colorado Rocky Mountain area and Cascade lake in Washington of USA, Khumbhu basin within Everest region of Nepal and Lirung outlet point of the same region of Nepal and much lower than the lakes of Spiti and Pandoh basins of India (Axtman and Stallard 1995;Reynolds et al 1995;Musselman et al 1996;Henriksen et al 1997;Tartari et al 1998;Bhatt et al 2000Das and Dhiman 2003;Borowiak et al 2006;Anshumali and Ramanathan 2007).…”
Section: Comparison Of Average Chemistry With Same and Different Basimentioning
confidence: 99%
See 1 more Smart Citation